2004
DOI: 10.1007/s00415-004-0296-4
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of oligoclonal bands in the CSF of patients with primary neurodegenerative dementia

Abstract: A central immune response can occur in primary neurodegenerative dementias, albeit uncommonly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 15 publications
2
13
0
2
Order By: Relevance
“…Likewise, Zimmermann et al [37] found intrathecal IgG synthesis in some of their AD patients without identifying a satisfying reason for the intrathecal humoral response. These findings were confirmed by Janssen et al [14] who observed positive OCB not only in AD but also in other dementias, including frontotemporal lobar degeneration (FTLD) and Creutzfeldt–Jakob disease. In motor neuron diseases (MND), elevated levels of CSF total protein, Q alb , and the presence of intrathecally IgG synthesis were observed [3, 31].…”
Section: Introductionsupporting
confidence: 70%
“…Likewise, Zimmermann et al [37] found intrathecal IgG synthesis in some of their AD patients without identifying a satisfying reason for the intrathecal humoral response. These findings were confirmed by Janssen et al [14] who observed positive OCB not only in AD but also in other dementias, including frontotemporal lobar degeneration (FTLD) and Creutzfeldt–Jakob disease. In motor neuron diseases (MND), elevated levels of CSF total protein, Q alb , and the presence of intrathecally IgG synthesis were observed [3, 31].…”
Section: Introductionsupporting
confidence: 70%
“…Intrathecally synthesized IgG as an indicator of an humoral immune response within the CNS occurring in 2% of our ALS population might be an unspecific alteration, which is also found in other neurodegenerative diseases in some 6-9% [19]. We suggest that intrathecal synthesis of antibodies might be a secondary event in a subgroup of ALS patients during the course of the disease.…”
Section: Discussionmentioning
confidence: 91%
“…Nine out of 20 multiple sclerosis patients had an IgG index above the designated cut-off value. Isoelectric focusing in context with clinical data appears to be a more sensitive diagnostic tool for differentiating multiple sclerosis and other neurodegenerative disorders [39]. A recent report by Sadaba and coworkers indicates that use of a single antibody conjugated to alkaline phosphatase provides an ultra sensitive method for detection of oligoclonal bands [40].…”
Section: Multiple Sclerosismentioning
confidence: 97%
“…Dementia/AD/amyloid disorders Aβ(1-42), Tau, phospho-Tau, apolipoprotein A1/E/J, α1b-glycoprotein, β2-microglobulin, RBP, TTR, kininogen, ubiquitin, β-trace, cell cycle progression 8 protein, α1-antitrypsin, α-2-HS glycoprotein, transferrin, cystatin C, VGF fragment, neuropeptide Y, 7.7 kD unknown peptide, secretogranins [18,19,22,[25][26][27] [28, [29][30][31][32][33][34][35][36] Multiple sclerosis 2+ oligoclonal IgG bands, Tau, psoriasin, NB-1, annexin 1, EWI-2, NPC-2, SEM1, SEM2, FHR-1, PCPE, aldolase A, N-acetyllactosaminide-β-1, 3-N-acetylglucosaminyltransferase, TETN, cystatin A, SOD3, glutathione peroxidase [9,10,[37][38][39][40] PCD and cancer anti-Yo, anti-Hu, N-myc, l-CaD, α-2-HS glycoprotein [3,74,75] Schizophrenia N-CAM [80] Creutzfeldt-Jakob disease 14-3-3, cystatin C [11,56] Rhinorrhea β2 transferrin [43][44][45] Low back pain PRO2619, PEDF, kallikrein-6 precursor, albumin homolog, DJ771712.1, AMBP protein precursor [2] Moyamoya disease CRABP-1 [59] Parkinson's disease TNF-α, IL-1β, IL-2, IL-4, IL-6, TGF-α, TGF-β1, TGF-β2, NGF, BDNF, NNMT [84][85][86][87][88][89][90] Stroke UFD1, UCH-L1, CATD, glutathione S-transferase P-1, DJ-1, NDKA, PPIA, PDX5, GFAP, CAYP, prostaglandin D2 synthase, S100, multiple FABPs [60][61]…”
Section: Neurologic Conditionmentioning
confidence: 99%